I Want to Live More : Self-Talk Under the Pressure of Breast Cancer - Brigita Vilč; Emilia Mazurek; Renata Martinec; Ivan Milas; Goran Šimić; Marina Šagud (Qualitative Health Research, 2026)
In this study, self-talk is conceptualized as a self-regulatory intrapersonal communication process that integrates emotional, cognitive, and social dimensions. Unlike prior studies that focus on the frequency or valence of self-talk, as well as the effectiveness of psychoeducational interventions, nearly always using quantitative methods, this study uses a qualitative approach to identify dynamic transitions and socio-contextual embedding of self-talk across the breast cancer trajectory. Adopting the interpretive paradigm, the qualitative study was conducted in Poland and Croatia. Data were gathered through in-depth interviews and lifeline drawings from a purposive sample of 24 breast cancer patients aged 34–76. As a result of reflexive thematic analysis, five interconnected themes were developed: embodied experience of illness, emotional roller coaster, cognitive and control-oriented strategies, socio-contextual self-talk, and dynamics of transitions in self-talk. They represent the multidimensional nature of self-talk, spanning somatic, emotional, cognitive, spiritual, and social spheres. Self-talk remains emotional, memorable, and open to reconstruction, as well as variable and dynamic throughout the cancer trajectory. It fulfills regulatory functions such as monitoring, evaluation, and behavioral guidance, encompassing both current events and strategic preparation for future challenges. The content, function, and context of self-talk should be jointly assessed to clarify its adaptive vs. maladaptive roles in populations with illness. Adaptive self-talk is characterized as self-supporting and self-compassionate; goal-driven, action-oriented, and task-focused; time-bound; and self-distanced. Maladaptive self-talk is self-critical, repetitive, associated with a loss of control, future-oriented rumination, and self-immersion. The results provide guidance for educating patients and clinicians on self-talk.